Study of Literature on Risk Management for Employee Health and Safety in Construction Projects - Afanda, Delia Monica; Lendra, Lendra; Kristiana, Wita (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Assessing possible risks in construction projects helps predict risks and plan risk management strategies. In construction projects, many factors can affect project completion, including the risk of work accidents. This research aims to look for Occupational Health and Safety risk factors for COVID-19 in construction projects by conducting a literature study on several previous studies. The research methodology is a literature search using the Publish or Perish application. Relevant literature is then used as a source of research. Based on the results of a literature study, twenty-eight risk factors are considered to have the potential to occur in construction projects consisting of eighteen OHS risk factors and ten COVID-19 risk factors. The five most common risk factors for OHS in previous studies were: falling from a height, being hit by material, being electrocuted, being scratched by workers, being punctured by material, and being hit by heavy equipment.